O relicário de uma professora alfabetizadora: a escrita infantil e o conhecimento na formação inicial docente - TEIXEIRA, Denise Letícia do Nascimento (2020)
The initial act of learning to read and write is a process that involves several methodological conceptions, which aim at achieving the literacy of elementary school students. With the intention of understanding the processes that involve literacy, the present work results in presenting the possibilities and limits about an educational practice of literacy, of a Municipal teaching institution of the metropolitan region of Belém, Pará. Develops through a qualitative, participant observation approach, with direct link to the Institutional Program of Initiation Scholarships (Pibid), in which the present author was trainee during the period of 1 year and 6 months. Since then, literacy activities have been developed with the students of the 2nd year of elementary school I, through the PPA (Pedagogical Support Project for Children with Learning Difficulties), in which it is carried out through the post-constructivist conception of the group GEEMPA (Study Group on Education, Research Methodology and Action). When analyzing the activities around the children's writings, we note the power that involves this work, however, the limit that occurs in this practice, as in any other pedagogical teaching practice, should not be dissociated. Therefore, to study, to understand, to analyze a vision of teaching is to delve into its theory and pedagogical practice, to reflect on the meeting of practice and theory and to reformulate ideas.